CONTRA-EDUCAÇÃO: UMA REFLEXÃO SOBRE ÉTICA E EDUCAÇÃO - Marcia Tiburi (Universidade do Oeste Paulista, 2013)
The article aims to establish conceptual links between education and ethics from a reflection on theory and practice, thought and action. Intends to show that this relationship goes beyond a theoretical tight, placing herself as construction moved by an impulse ethical. Thus, this article guard his own theory and want to express the importance of self-practical understanding of ethical theories, and theories of education. In the intention to substantiate the relationship between theory and practice, the paper discusses the theories of some authors who have addressed the question of the social role of education, such as István Mészáros and Humberto Maturana. The subject of ethics education as the means of education as emancipation which became known from the writings of Theodor Adorno. The path to awakening of an education as ethics goes through critical discourse capable of staging the importance of dialogue. The ultimate intention of this article is, therefore, favor the construction of a concept of education as ethics from the idea of dialogue as emancipation, while reproposes emancipation as a principle and method of education themselves. In this context, the analysis is positioning education as a discourse, as conservation practice, against which we must now propose the hypothesis of a counter-practice education. The development expression of counter-education is presented here 36 Colloquium Humanarum, Presidente Prudente, v. 10, n. 1, p.35-57, jan/jun 2013. DOI: 10.5747/ch.2013.v10.n1.h136 in its initial signs yet. However, it want to with it, pointing to the opening of a necessary discussion in education.